PENGEMBANGAN SUMBER DAYA MANUSIA - Samsuni Samsuni (CV. ADIBA AISHA AMIRA, 2025)
Human resources (HR) is one of the most important factors that cannot be separated from an organisation, both institutions and companies. HR is also the key that determines the development of the company. In essence, human resources are people employed in an organisation as movers, thinkers and planners to achieve the organisation's goals. Nowadays, the latest developments view employees not as mere resources, but rather as capital or assets for institutions or organisations. Because of this, a new term emerged outside of H.R. (Human Resources), namely H.C. or Human Capital. This is where human resources are seen not just as the main asset, but an asset that is valuable and can be multiplied, developed and also not otherwise as a liability (burden or cost). Here it is necessary to develop human resources as an investment for the institution or organisation to be improved